Interleukin-37 ameliorates myocardial ischaemia/reperfusion injury in mice. (24th April 2014) - Wu, B; Meng, K; Ji, Q; Cheng, M; Yu, K; Zhao, X; Tony, H; Liu, Y; Zhou, Y; Chang, C; Zhong, Y; Zhu, Z; et al.
Summary: Innate immune and inflammatory responses are involved in myocardial ischaemia/reperfusion (I/R) injury. Interleukin (IL)-37 is a newly identified member of the IL-1 family, and functions as a fundamental inhibitor of innate immunity and inflammation. However, its role in myocardial I/R injury remains unknown. I/R or sham operations were performed on male C57BL/6J mice. I/R mice received an injection of recombinant human IL-37 or vehicle, immediately before reperfusion. Compared with vehicle treatment, mice treated with IL-37 showed an obvious amelioration of the I/R injury, as demonstrated by reduced infarct size, decreased cardiac troponin T level and improved cardiac function. This protective effect was associated with the ability of IL-37 to suppress production of proinflammatory cytokines, chemokines and neutrophil infiltration, which together contributed to a decrease in cardiomyocyte apoptosis and reactive oxygen species (ROS) generation. In addition, we found that IL-37 inhibited the up-regulation of Toll-like receptor (TLR)-4 expression and nuclear factor kappa B (NF-kB) activation after I/R, while increasing the anti-inflammatory IL-10 level. Moreover, the administration of anti-IL-10R antibody abolished the protective effects of IL-37 in I/R injury. In-vitro experiments further demonstrated that IL-37 protected cardiomyocytes from apoptosis under I/R condition, and suppressed the migration ability of neutrophils towards the chemokine LIX. In conclusion, IL-37 plays a protective role against mouse myocardial I/R injury, offering a promising therapeutic medium for myocardial I/R injury.